1993
DOI: 10.1103/physrevlett.71.4059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substitution of Zn for Cu in the spin-Peierls cuprate,CuGeO3: The suppression of the spin-Peierls transition and the occurrence of a new spin-glass state

Abstract: The magnetic susceptibilities of polycrystalline Cuix Zn x Ge03 were measured to study the effects of nonmagnetic impurities on the spin-Peierls transition. The transition temperature drastically reduces upon Zn doping and the spin-Peierls state collapses around x=0.03. The Zn doping causes another phase transition in the samples with 0.02

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
252
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 311 publications
(269 citation statements)
references
References 19 publications
12
252
2
Order By: Relevance
“…Investigations have concentrated on systems where Cu atoms were replaced with Zn [14][15][16][17][18][19] or Ge was replaced with Si. [20][21][22] It is now well established that a new antiferromagnetic (AF) ordered phase appears at low temperatures in both Zn-doped 14,19 and Si-doped 22 samples. A preliminary phase diagram was determined from susceptibility measurements on powder samples 14 which showed that T SP decreases with increasing Zn concentration while the Néel temperature increases to T N ∼ 4K.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have concentrated on systems where Cu atoms were replaced with Zn [14][15][16][17][18][19] or Ge was replaced with Si. [20][21][22] It is now well established that a new antiferromagnetic (AF) ordered phase appears at low temperatures in both Zn-doped 14,19 and Si-doped 22 samples. A preliminary phase diagram was determined from susceptibility measurements on powder samples 14 which showed that T SP decreases with increasing Zn concentration while the Néel temperature increases to T N ∼ 4K.…”
Section: Introductionmentioning
confidence: 99%
“…For specific compounds and doping conditions, certain predictions of the model, such as phase transitions or long-range ordering, have been experimentally tested, either by the measurement of macroscopic quantities 22,24,25 or by scattering techniques 23,[26][27][28] . However, some configurations are difficult to investigate experimentally, such as the impact of boundaries 29 or spatial variations in the coupling or dimerization strength.…”
mentioning
confidence: 99%
“…[7][8][9] The discovery of the inorganic SP compound CuGeO 3 (Ref. 10) opened the way to impurity substitiution and it turned out that just a small amount of the impurity modifies the phase diagram to a more complicated one; 11,12 with decreasing temperature, after the appearance of D phase at T SP , the system shows another transition to a peculiar ordered phase, where antiferromagnetic (AF) long-range order and the SP order coexist [dimerized AF (D-AF) phase]. 13 The staggered moment and the lattice deformation are spatially modulated in D-AF phase; the amplitude is larger near the impurity sites and smaller in between them.…”
Section: Introductionmentioning
confidence: 99%